2008
DOI: 10.4315/0362-028x-71.7.1442
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Toxoplasma gondii Risk in Ready-to-Eat Smallgoods Processing

Abstract: Toxoplasma gondii is one of the most common parasitic infections of humans and other warm-blooded animals. In most adults, it does not cause serious illness, but severe disease may result from infection in fetuses and immunocompromised people. Consumption of raw or undercooked meats has consistently been identified as an important source of exposure to T. gondii. Several studies indicate the potential failure to inactivate T. gondii in the processes of cured meat products, This article presents a qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 53 publications
0
18
0
2
Order By: Relevance
“…In relation to the other product analyzed, dry-cured ham, there is little knowledge of the effects of several processing conditions on the inactivation of the parasite, such as organic acids, nitrites and nitrates, or the combination of salt concentration, time, and temperature during its maturation (24). Sommer et al (25) showed that encysted T. gondii survived for 4 days in 8% NaCl, but neither this group nor Work (28) could demonstrate viable parasites in T. gondii-infected pork subjected to various curing processes.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the other product analyzed, dry-cured ham, there is little knowledge of the effects of several processing conditions on the inactivation of the parasite, such as organic acids, nitrites and nitrates, or the combination of salt concentration, time, and temperature during its maturation (24). Sommer et al (25) showed that encysted T. gondii survived for 4 days in 8% NaCl, but neither this group nor Work (28) could demonstrate viable parasites in T. gondii-infected pork subjected to various curing processes.…”
Section: Discussionmentioning
confidence: 99%
“…G. lamblia) 7) , Toxoplasma gondii 8,9) , Anisakis spp. 10) , Trichinella spiralis 11,12) , Taenia solium cysticercus 13) , and Taenia saginata 14) .…”
Section: Introductionunclassified
“…10) , Trichinella spiralis 11,12) , Taenia solium cysticercus 13) , and Taenia saginata 14) . In these studies, most of the risk assessments employed quantitative approaches, such as probabilistic analysis using Monte Carlo modeling 5,14) , hazard impact analysis 6,7,9) , scoring risks 8) , risk profiling 10,11,13) , and exposure assessment 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue cysts are the terminal lifecycle stage in the intermediate host and are immediately infective. In some intermediate host species, including most livestock, they may persist for the life of the host, being consumption of raw or undercooked meat products containing tissue cysts a major risk factor associated with human toxoplasmosis (Dubey & Beattie, 1988;García et al, 2006;Hill, 2007;Mie et al, 2008). Toxoplasma has historically been associated with pork meat but a recent case-control study by CDC found the leading foodborne risks to be eating raw ground beef, rare lamb or locally-produced cured, dried or smoked meat (Jones et al, 2009).…”
Section: Introductionmentioning
confidence: 99%